P3.402 Effect of a Tailored Intervention Package on HIV-1 Acquisition Among Young Female Sex Workers in Ouagadougou, Burkina Faso. (13th July 2013) - Traore, I T; Hema, M N; Meda, N; Konate, I; Some, F; Bazie, W; Mayaud, P; Perre, P Van De; Nagot, N
Abstract : Background: Female Sex Workers (FSWs) represent a major core group of HIV transmission in West Africa, but little data is available on the impact of tailored intervention packages on HIV-1 incidence in this population. Method: HIV-seronegative young women aged 18–25 years, living in Ouagadougou, reporting at least 3 sexual contacts per week and 3 different sexual partners during the last 3 months, and not pregnant were enrolled in a prospective cohort. At each 3-months follow-up visit for a minimum period of 12 months, data on sexual behaviour, HIV-1 and HSV-2 serologies and pregnancy testing were collected. The intervention used a tailored prevention-and-care integrated approach, with repeated peer-led HIV/STI education sessions, condoms provision, and medical care. HIV incidence was compared with an expected incidence based on baseline data among FSW and data from the national 2010 DHS. In Ouagadougou, 2.5% (95% CI: 1.5–3.4) of women and 3.4% (95% CI: 1.3–5.5) of FSW clients were HIV-1 infected. Results: At screening, HIV prevalence among eligible women was 9% (55/638), and 321 women were enrolled. The median weekly number of sexual partners (clients and regular partners) was 3 (IQR: 2–5). During follow-up, 86% of participants completed 12-months follow-up and no woman seroconverted for HIV-1 (0/405 person-years, 95% CI: 0–0.03). The mean number of regular partners decreased during the intervention (from 2 to 1, p < 0.001). Adjusted consistent condom use remained consistently very high with clients between 97% and 99%), and did not increase with regular partners (from 64 to 62%). The incidence of HSV-2 was 11/100 person-years (95% CI: 7–15), and the pregnancy rate was 28/100 person-years (95% CI: 23–32). The expected HIV-1 incidence in this group was 1.23/100 person-years (95% CI: 1.02–1.46). Conclusion: Through an impact on the number of regular partners, this tailored intervention package markedly reduced HIV incidence to virtual elimination.